2007
DOI: 10.1002/mrc.2017
|View full text |Cite
|
Sign up to set email alerts
|

Configurational assignment of carbon, silicon and germanium containing propynal oximes by means of 13C1H, 13C13C and 15N1H spin–spin coupling constants

Abstract: Configurational assignment of five carbon, silicon and germanium containing propynal oximes has been carried out by means of experimental measurements and high-level ab initio calculations of their 13C-1H, 13C-13C and 15N-1H spin-spin coupling constants. The title compounds were shown to exist in the nonequilibrium mixture of E and Z isomers with the energy difference of less than 0.3 kcal/mol calculated at the MP2/6-311G** level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…It is remarkable that the nitrogen lone pair orientation effect in 1-vinylpyrrole-2-carbaldehyde oxime1 is significantly smaller than that in the other aldoximes. [3,4,7,10] Besides, one can see the dramatic difference between the 2 J(N-2', H-1') coupling constants in the 1-E and the 1-Z isomers. The 2 J(N-2', H-1') coupling constant is by as much as 7 times larger in the absolute size in the 1-Z isomer (Table 4) revealing the variable contribution from nitrogen lone pair to this coupling in the configurational isomers of aldoximes.…”
Section: N Chemical Shiftsmentioning
confidence: 94%
See 1 more Smart Citation
“…It is remarkable that the nitrogen lone pair orientation effect in 1-vinylpyrrole-2-carbaldehyde oxime1 is significantly smaller than that in the other aldoximes. [3,4,7,10] Besides, one can see the dramatic difference between the 2 J(N-2', H-1') coupling constants in the 1-E and the 1-Z isomers. The 2 J(N-2', H-1') coupling constant is by as much as 7 times larger in the absolute size in the 1-Z isomer (Table 4) revealing the variable contribution from nitrogen lone pair to this coupling in the configurational isomers of aldoximes.…”
Section: N Chemical Shiftsmentioning
confidence: 94%
“…Recently, such an effect was successfully employed to carry out the configurational assignment of the new silicon and germanium containing propynal aldoxime. [10] N-Vinylpyrroles were thoroughly studied from an NMR spectroscopic viewpoint. It was shown that both shielding and spin-spin coupling constants were sensitive to the stereo-orientation of the vinyl group relative to the pyrrole ring.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Also, an unusually large orientational effect of the nitrogen lone pair on the 1 J(C,C) coupling constant (13-16 Hz) was found in these compounds. [11] Further investigation of the 13 C NMR spectra for series of oximes with a heteroaryl substituent discovered that the shielding constants of the double bond carbons (C-2 and C-3, Scheme 1) reveal the same stereospecificity in the configurational isomers as those of the triple bond carbons in the propynal oxime (C-2 and C-3, Scheme 1) [13,14] indicating the common character of the stereospecific effect on the carbon shielding constants in the configurational isomers of the conjugated oximes.…”
Section: Introductionmentioning
confidence: 97%
“…[11,12] In order to develop an idea about the stereospecificity of the 13 C shielding constants in the oximes having a substituent with triple bond, in this work, the silicon and germanium containing acetylenic ketoximes were synthesized and their 13 C NMR spectra were studied. A comparative analysis of 13 C shielding constants stereospecificity in the acetylenic aldoximes and ketoximes was carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation